Electric-field-induced lamellar to hexagonally perforated lamellar transition in diblock copolymer thin films: kinetic pathways. Issue 36 (5th September 2016) - Mukherjee, Arnab; Ankit, Kumar; Reiter, Andreas; Selzer, Michael; Nestler, Britta
Abstract : In this work, the confluence of an electric field, substrate interaction and confinement is shown to induce a parallel lamellar to hexagonally perforated lamellar transition in symmetric block-copolymer thin films. Abstract : Symmetric block-copolymers, hitherto, are well known to evolve into parallel, perpendicular and mixed lamellar morphologies under the concomitant influence of an electric field and substrate affinity. In the present work, we show that an additional imposed confinement can effectuate a novel parallel lamellar to hexagonally perforated lamellar (HPL) transition in monolayer and bilayer films. Three dimensional numerical studies are performed using the Ohta–Kawasaki functional, complemented with an exact solution of Maxwell's equation. HPL is shown to stabilize at large substrate affinity in a narrow region of the phase diagram between parallel and perpendicular lamellar transitions in ultra-thin films. Additionally, we also identify perforated lamellae as intermediate structures during parallel-to-perpendicular lamellar transition. A systematic analysis using Minkowski functionals yields deeper insights into the associated kinetic pathways.